Wallander. Season 4 [videorecording (DVD)] - Branagh, Kenneth; Warner, David, 1941-; Spark, Jeany, 1982-; Mankell, Henning, 1948-2015; Mankell, Henning, 1948-2015; Mankell, Henning, 1948-2015; McCabe, Richard (British Broadcasting Corp. : BBC Video, 2016)
In The White Lioness, Wallander is drawn into the case of a missing Swedish national while attending a police conference in South Africa. The second film sees Wallander back in Sweden, where a woman's body is discovered half buried in the forest swamps. And in The Troubled Man, Wallander is in a race against time as he embarks on his final case - the disappearance of his daughter's father-in-law.